Predicting the spatial distribution of water applied by subsurface drip in clay soil - Mayara O. Rocha; Amilton G. S. de Miranda; Policarpo A. da Silva; Adunias dos S. Teixeira; Fernando F. da Cunha (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In subsurface drip irrigation systems, knowledge of the three-dimensional advancement of water in the soil is essential for selecting emitter spacing and installation depth. This research aimed to develop and test different mathematical models to estimate water distribution in the soil under subsurface drip irrigation. The experiment was set up in a completely randomized design with four replicates. The experimental arrangement was of split-plot in time, with different dripper installation depths in the plots (0, 5, 10, 15, 20, 25, and 30 cm) and in the subplots irrigation application times (0, 60, 120, 180, and 240 min). Three models (SLIDE 6.0, polynomial regression, and SPSS 2.0) were constructed to estimate the water distribution in the soil profile. All models showed statistical indexes within acceptable ranges. In comparison, the model generated in the numerical software SLIDE 6.0 was the one that presented the best performance, followed by SPSS 2.0 and polynomial regression. The generated models were efficient and simple, producing good results in predicting the water distribution in the soil profile under the studied conditions.